2012 - Kloser, Harald, 1956-; Gordon, Mark, 1956-; Franco, Larry J.; Emmerich, Roland; Cusack, John, 1966-; Ejiofor, Chiwetel, 1974-; Peet, Amanda, 1972-; Platt, Oliver; Newton, Thandie, 1972-; Glover, Danny; Harrelson, Woody; Wander, Thomas; et al. (Culver City, Calif : Sony Pictures Home Entertainment, 2010)
A geophysical team, who are investigating the effect radiation from other solar systems has on the Earth, learn that the core of the Earth is heating up and warn the President of the United States. While the leaders of the world race to build 'arks' to escape the impending doom, volcanic eruptions and earthquakes of unprecedented strength wreak havoc all over the world.
Originally released as a motion picture in 2009.
Special features: Commentary with writer/director Roland Emmerich and co-writer Harald Kloser; alternate ending; deleted scenes; "Roland Emmerich: the master of the modern epic" featurette; music video "Time for miracles" by Adam Lambert.
Director of photography, Dean Semler ; editors, David Brenner, Peter S. Elliott ; music, Harald Kloser, Thomas Wander.
John Cusack, Chiwetel Ejiofor, Amanda Peet, Oliver Platt, Thandie Newton, Danny Glover, Woody Harrelson.
MPAA rating: PG-13; for intense disaster sequences and some language.
DVD, region 1, anamorphic widescreen (2.40:1) presentation; Dolby Digital 5.1 surround.
Keywords: Two thousand twelve, A.D. -- Drama; Geophysical prediction -- Drama; End of the world -- Drama; Survivalism -- Drama; Environmental degradation -- Drama; Earth -- Core -- Drama